PERATURAN PERUNDANGAN DAN IMPLEMENTASI PENDIDIKAN INKLUSIF - Titik Handayani; Angga Sisca Rahadian (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2013)
This article discusses issues related to the regulation and implementation of inclusive education. Inclusive education is an effort to provide access to education for all citizens, including citizens with special needs. It reviews various legal products related to education and other relevant literature. It finds that the content of the provisions of various laws, regulations and ministerial regulations have not fully addressed inclusive education as one of the approaches and principles in education in Indonesia. At the level of implementation, these legal products also contained discrimination for students with special needs, which is contrary to the nature and basic principles of inclusive education. Beyond regulations, there are many problems, including the lack of facilities and infrastructure, lack of teachers, rigid curriculum, and low public support for inclusive education. Therefore, in advance Indonesia needs to reform educational policy in order to meet inclusive education goal.Keywords: Inclusive Education, Regulatory Problems, Discrimination.